Exploring the Roles of IPOs and Main Bank Relationships on Debt Maturity: The Case of Japan - Jieting Chen; Jinbin Fan (International Journal of Financial Studies)
The choice between short- and long-term debt impacts a firm’s financial flexibility and its capacity for sustainable investment. This study examines how Initial Public Offerings (IPOs) and main bank relationships shape debt maturity structures, focusing on Japanese firms listed on the Tokyo Stock Exchange between 2002 and 2015. Using panel fixed effects and difference-in-differences (DID) analysis, we find a temporary extension in debt maturity (i.e., a reduction in the short-term debt ratio) one year post-IPO. Our findings partially support the hypothesis under signaling theory, which states that firms can mitigate asymmetric information problems through IPOs, facilitating the issuance of long-term debt, and thus allowing firms to allocate resources for sustainability projects. Notably, Japanese firms without a main bank relationship experience a more significant and lasting impact, while those with a main bank relationship display minimal changes in debt structure. These findings highlight the critical role of Japanese institutional factors in alleviating information asymmetry and enabling access to long-term financing. Additionally, the findings enlighten studies on financial mechanisms that enable firms to align their strategies with Sustainable Development Goals (SDGs) in the long run.